2003
DOI: 10.1167/iovs.02-0707
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sp1/Sp3 Expression on Corneal Epithelial Cells Proliferation and Differentiation Properties in Reconstructed Tissues

Abstract: Expression of Sp1/Sp3 may represent a good predictor for selecting HCECs that are most likely to proliferate, stratify, and differentiate properly when used for the production of reconstructed corneal substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…For example, Gaudreault et al identified the expression of a series of transcription factors known as specificity protein 1 and 3 (Sp1/Sp3) as good predictive indicators of corneal epithelial cell proliferation. 11 While such molecular approaches are useful and give an insight into the mechanisms that govern corneal epithelial cell proliferation and migration they are of limited value in the practical setting of an eye bank.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gaudreault et al identified the expression of a series of transcription factors known as specificity protein 1 and 3 (Sp1/Sp3) as good predictive indicators of corneal epithelial cell proliferation. 11 While such molecular approaches are useful and give an insight into the mechanisms that govern corneal epithelial cell proliferation and migration they are of limited value in the practical setting of an eye bank.…”
Section: Discussionmentioning
confidence: 99%
“…8 Indeed, in the absence of fibroblasts, keratinocytes are disorganized and poorly attach to the dermis, whereas good attachment, remodeling of the basement membrane, and appropriate epithelial organization, including stem cell preservation, occur when fibroblasts are present. [9][10][11][12] As documented for human corneal epithelial cells, 13 monolayers of human skin keratinocytes with appropriate morphological and proliferative properties are also absolutely required prior to their seeding onto the reconstructed extracellular matrix in order to ensure their persistence, as well as an appropriate cuboidal basal layer and vertical stratification on the tissue-engineered skin substitute. Because they depend on mesenchymal cell interactions, keratinocytes used for clinical purposes must be co-cultured along with growth-arrested, γ-irradiated mouse 3T3 fibroblasts (i3T3) as a feeder layer.…”
Section: Introductionmentioning
confidence: 99%
“…Gaudreault et al, 13 for example, used ascorbic acid to promote the production of collagen and other ECM molecules by dermal fibroblast cells. The resulting ECM sheets are then stacked together to form a stroma, and allowed to further integrate in culture, after which an epithelium is seeded on top of the stack.…”
Section: Self-assembled Corneal Substitutesmentioning
confidence: 99%